Handbook of biofuels production : processes and technologies - Luque, Rafael; Campelo, Juan; Clark, James H. (Woodhead Publishing in energy ;, 2011)
In response to the global increase in the use of biofuels as substitute transportation fuels, advanced chemical, biochemical and thermochemical biofuels production routes are fast being developed. Research and development in this field is aimed at improving the quality and environmental impact of biofuels production, as well as the overall efficiency and output of biofuels production plants. The range of biofuels has also increased to supplement bioethanol and biodiesel production, with market developments leading to the increased production and utilisation of such biofuels as biosyngas.